Relation of Waist Hip Ratio and BMI with the Vital Capacity - Karmacharya, Poonam; Shrestha, Gopi Lal; Singh, Surjit; Shrestha, Om Kumar (Journal of Chitwan Medical College, 2019)
Background: The body mass Index and waist hip ratio have shown to have linear relation with increase in vital capacity. The purpose of the study is to find the relation of both BMI and waist hip ratio with the vital capacity. Methods: In this prospective cross-sectional study, 240 students from Manipal College of medical sciences, Pokhara were enrolled. Respiratory function was assessed by student’s spirometer. The mean of three reading was noted as reading for vital capacity. Height, weight, waist and hip measurement was done. The data were used to derive BMI and the waist hip ratio. Data analysis was done with spss17. The Pearson’s correlation test was applied for correlating vital capacity with the anthropometric measures considered. Results: Out of 240 students 59% were male and 41% were female. There was no correlation between BMI and vital capacity and also between Waist-hip ratio and vital capacity. Conclusions: The study revealed that anthropometric and body compositions are not predictors of respiratory muscle strength.